(untitled) (Balthazar, 2025)
The power of photography, its strength and its limits, were the subject of Susan Sontag’s (1933-2004) attention mainly thanks to her two famous contributions on the subject: On Photography, published in 1977 as a collation of previously published texts in the “New York Review of Books”, and Regarding the Pain of Others published in 2003, shortly before the untimely death of the American writer and activist. The essays on photography that Susan Sontag left us have marked decades of visual culture, both in Italy and abroad, of discussions and reflections on the capacity of this medium to shape consciousness, modify perceptions, and condition information. And while it is true that the theme of the voyeurism of the photographic gaze was explored in depth in the 2003 essay on the experience of the brutal trauma of the fruition of war through images, it is above all the 1977 essay that is still considered a point of reference for a new way of reading and thinking about photography, placed in transversal and dynamic dialogue with other disciplines, first and foremost cinema. This contribution aims to return to rereading the origins of the theme of photographic voyeurism in Susan Sontag’s thought, then declining it in her reading of Diane Arbus’ poetics as a complex, fascinating, controversial case study.